Improvement of transient performance and power efficiency of a variable-speed compressor refrigeration system using anti-windup control methodology. (2018)
(Eng) This paper presents a control methodology to improve the transient performance and power efficiency of a refrigeration system that uses a variable-speed compressor. The control objective is to maintain the compartment temperature at the desired setpoint, despite varying heat load conditions or disturbances. A model of the refrigeration system was obtained. The variables of interest were the compartment temperature, the evaporator superheat temperature, and the speed of the variable-speed compressor. By using simulations and real tests of the refrigeration system, it was found that a conven - tional implementation of a closed-loop controller causes a phenomenon known as windup, which leads to variable-speed compressor saturation and diminishes the transient performance of the refrigeration system and increases power con - sumption. Additionally, the evaporator superheat temperature was not significantly affected by the speed of the variable compressor, so the only option for improving the coefficient of performance of the refrigeration system was reducing the power consumption of the variable-speed compressor. An anti-windup topology for the closed-loop controller was proposed to prevent variable-speed compressor saturation. Simulations and tests of the refrigeration system showed an important improvement of the transient performance and power efficiency of the refrigeration system.